Multimodal Surgical Management of Cerebral Lesions in Motor-Eloquent Areas Combining Intraoperative 3D Ultrasound with Neurophysiological Mapping - Policicchio, Domenico; Ticca, Stefano; Dipellegrini, Giosuè; Doda, Artan; Muggianu, Giampiero; Boccaletti, Riccardo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background Resection of tumors adjacent to motor pathways carries risks of both postoperative motor deficit and incomplete resection. Our aim was to assess usefulness and limitations of a multimodal strategy that combines intraoperative ultrasound (iUS) guided resection with intraoperative neurophysiology.Methodology This is a prospective study of 25 patients with brain lesions adjacent to motor areas who underwent intracranial surgery with assistance of the iUS guidance system and intraoperative neurophysiological monitoring and mapping. Pathologies treated included 19 gliomas, 3 metastases, 1 anaplastic meningioma, 1 arteriovenous malformation (AVM), and 1 ependymoma. The iUS-guided lesion removal accuracy and the extent of resection were estimated and compared with a 30-day postoperative brain MRI. The results were assessed considering the extent of resection related to 6-month motor function outcome.Results iUS was accurate in checking the extent of resection in 17 patients, whereas in 8 cases the decline of the iUS images quality did not allow a valuable assessment. Positive mapping was obtained in 16 patients. Gross total resection was achieved in 16 patients. In five of nine cases with subtotal resection, surgery was stopped because a functional area was reached. In four patients, tumor removal was limited due to the difficulty of identifying neoplastic tissue. Motor function worsening was transient in six patients and permanent in two.Conclusions The integrated use of intraoperative neuromonitoring to identify motor areas and iUS to identify tumor–tissue interface could help increase the rate of radical resection respecting the eloquent areas.
Keywords: intraoperative 3D ultrasound; US-guided brain surgery; cortical stimulation; brain mapping; brain tumors